Targeted immune activation in pediatric solid tumors: opportunities to complement local control approaches - Vonderhaar, Emily P.; Dwinell, Michael B.; Craig, Brian T. (Frontiers in Immunology, 2023)
Surgery or radiation therapy is nearly universally applied for pediatric solid tumors. In many cases, in diverse tumor types, distant metastatic disease is present and evades surgery or radiation. The systemic host response to these local control modalities may lead to a suppression of antitumor immunity, with potential negative impact on the clinical outcomes for patients in this scenario. Emerging evidence suggests that the perioperative immune responses to surgery or radiation can be modulated therapeutically to preserve anti-tumor immunity, with the added benefit of preventing these local control approaches from serving as pro-tumorigenic stimuli. To realize the potential benefit of therapeutic modulation of the systemic response to surgery or radiation on distant disease that evades these modalities, a detailed knowledge of the tumor-specific immunology as well as the immune responses to surgery and radiation is imperative. In this Review we highlight the current understanding of the tumor immune microenvironment for the most common peripheral pediatric solid tumors, the immune responses to surgery and radiation, and current evidence that supports the potential use of immune activating agents in the perioperative window. Finally, we define existing knowledge gaps that limit the current translational potential of modulating perioperative immunity to achieve effective anti-tumor outcomes.